Optimized Circularly Polarized Patch Antenna with Horizontal and Side Slots for UHF RFID Readers - Wichakoon, Worathan; Nuangwongsa, Kanawat; Phongcharoenpanich, Chuwong (My University, 2025)
This paper presents the design and optimization of a circularly polarized UHF RFID reader antenna. The initial radiator dimensions were set at 130 mm × 130 mm, and the feed position was fine-tuned, with simulations identifying x, y = 24.5, 24.5 mm as the optimal location for impedance matching. Further optimization focused on reducing the ground plane size, with a 170 mm × 170 mm ground plane providing the optimal balance, ensuring an axial ratio below 3 dB and stable |S| (dB) response across the 920-925 MHz frequency band. The final design demonstrated an improved radiation pattern and sufficient gain, making it an effective solution for UHF RFID reader applications.
Keywords: circular polarization; Patch Antenna; RFID reader; slot antenna; UHF RFID